Residual activities of 99mTc-labelled radiopharmaceuticals in routine nuclear medicine practice. Issue 6 (June 2016) - Stavrou, Petros Z.; Papachristou, Maria; Persakis, Evangelos; Kouvelis, Konstantinos; Datseris, Ioannis E.
Abstract : Introduction: In this study, we present a series of common 99m Tc-labelled radiopharmaceuticals administrations performed in a busy nuclear medicine department within a 1-year timeframe in routine practice. The main objective is to identify the true activity administered to the patient and whether that is in compliance with the EANM guidelines, where applicable, and/or with the department's protocols. As a secondary objective, we aimed to assess whether the volume of the injected dose correlates to the percentage of residual activity measured after injection for each studied radiotracer. Materials and methods: A number of commonly used 99m Tc-labelled radiopharmaceuticals including 99m Tc-pertechnetate, 99m Tc-methylenediphosphonic acid, 99m Tc-hydroxymethylenediphosphonic acid, 99m Tc-3, 3-diphosphono-1, 2-propanedicarboxylic acid, 99m Tc-dimercaptosuccinic acid (DMSA), 99m Tc-mercaptoacetyltriglycine, 99m Tc-2-methoxyisobutylisonitrile (sestamibi), 99m Tc-1, 2-bis[bis(2-ethoxyethyl)phosphino]ethane (tetrofosmin) and 99m Tc-HYNIC-Tyr 3 -octreotide (Tektrotyd) were assessed. All data were collected prospectively within a 1-year period under routine medical practice and included (a) injected activity, (b) residual activity, (c) percentage of residual activity (residual activity/injected activity×100), (d) effective activity (injected activity minus the residual activity), (e) injected volume, (f) time of injection and (g) type of procedure. Results: In the 1837 collected measurements, the average percentage of residual activity was 13% (95% confidence interval: 12.75–13.39%). The mean effective activities were within the recommended range by the EANM guidelines, where applicable, or did not exceed the recommended doses from the department's protocols. In cases where actual injected activity was lower than the minimum suggested by the department's protocols, the imaging quality was not compromised. There was a negative correlation and thus an inverse relationship between the percentage of residual activity and administered volume for 99m Tc-pertechnetate, Teceos, Bonescan, HDP, generic DMSA, RENOCIS, Nephromag and Tektrotyd (Spearman's r coefficient ranging from −0.311 to −0.561). Cardiologic radiotracers presented no such correlation. Conclusion: It should be possible to reduce the level of administered activity for the diagnostic examinations, but with consideration of the residual activity, especially for radiopharmaceuticals with a high mean residual activity (mainly tetrofosmin and sestamibi).